Genetic Diversity of the Symbiotic Fungus Epichloë festucae in Naturally Occurring Host Grass Populations - von Cräutlein, Maria; Helander, Marjo; Korpelainen, Helena; Leinonen, Päivi Helena; Vázquez de Aldana, Beatriz R.; Young, Carolyn Anne; Zabalgogeazcoa, Iñigo; Saikkonen, Kari (Frontiers in Microbiology, 2021)
Epichloë festucae is a common symbiont of perennial and widely distributed cool season grass, Festuca rubra. The symbiosis is highly integrated involving systemic growth of the fungus throughout above-ground host parts and vertical transmission from plant to its offspring via host seeds. However, both the loss of fungus in the maternal host lineage and contagious spread by sexual spores within the host population may partly explain the detected variation in symbiosis in wild grass populations. Here we examined the population genetic structure of E. festucae to reveal the gene flow, importance of reproduction modes, and alkaloid potential of the symbiotic fungus in Europe. Epichloë-species are highly dependent on the host for survival and reproduction whilst benefits to the host are largely linked to defensive mutualism attributable to fungal-origin bioactive alkaloids that negatively affect vertebrate and/or invertebrate herbivores. We detected decreased genetic diversity in previously glaciated areas compared to non-glaciated regions and found three major genetic clusters in E. festucae populations: southern, northeastern and northwestern Europe. Sexual reproduction may have a higher role than expected in Spanish E. festucae populations due to the predominance of unique genotypes and presence of both mating types in the region. In contrast, asexual reproduction via host seeds predominates in Northern Europe due to the presence of biased mating-type ratios and large dominant genotypes in the E. festucae populations within the region. A substantially larger variation of alkaloid genotypes was observed in the fungal populations than expected, although the variability of the alkaloid genotypes within populations is considerably lower in northern than in Southern Europe. E. festucae populations consist of different combinations of alkaloid classes from the gene clusters of ergot alkaloid and indole-terpenes, and from pyrrolopyrazine alkaloid gene. We suggest that the postglacial distribution history of the host grass, prevailing reproduction strategies of E. festucae, and past and present herbivory likely explain a large part of the genetic variation observed in fungal populations among geographic regions. The identified alkaloid genotypes can be used by turfgrass breeders to improve resistance against herbivores in red fescue varieties and to develop new sustainable cultivars in Europe.